2022
DOI: 10.3389/fonc.2022.917541
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of indocyanine green near-infrared fluorescent imaging-guided lymph nodes dissection during radical gastrectomy for gastric cancer: A systematic review and meta-analysis

Abstract: BackgroundIndocyanine green (ICG) fluorescence imaging has been a new surgical navigation technique for gastric cancer. However, its clinical value should still be evaluated further. In this meta-analysis, we investigated the safety and efficacy of ICG near-infrared fluorescent imaging-guided lymph nodes (LNs) dissection during radical gastrectomy.MethodsStudies comparing ICG fluorescence imaging with standard care in patients with gastric cancer were systematically searched from PubMed, Embase, Web of Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Apart from the included literature, some indications were not reported because of the lack of quantitative assessment. For example, a large body of literature suggests the possibility of ICG-guided lymphadenectomy during gastrectomy [66,67]. The study by Okubo et al [68] indicates a difference in the intensity-to-background ratio between sentinel lymph nodes and non-sentinel lymph nodes in early gastric cancer and recommended intraoperative, quantitative measurement in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the included literature, some indications were not reported because of the lack of quantitative assessment. For example, a large body of literature suggests the possibility of ICG-guided lymphadenectomy during gastrectomy [66,67]. The study by Okubo et al [68] indicates a difference in the intensity-to-background ratio between sentinel lymph nodes and non-sentinel lymph nodes in early gastric cancer and recommended intraoperative, quantitative measurement in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical setting, we anticipate preoperative MRI will help plan lymphadenectomy by clearly highlighting occurrences where draining (magnetic) LNs are located outside of conventional surgical fields—for example, if D1 lymphadenectomy is planned but magnetic LNs are found in D2 stations. In combination with intraoperative lymphatic mapping by fluorescent ICG, this approach can provide clear differentiation of the draining lymphatic structures, reduce intraoperative bleeding [ 7 ], and provide surgical guidance to enable less experienced surgeons perform more targeted lymphatic resections (i.e. SNNS), which potentially results in reduced patient morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, a much more specific and targeted approach to staging LN metastases could be beneficial [ 4 6 ], thereby creating a role for an accurate means of SLN localization in gastric cancer prognosis and treatment. While SLNB concepts, such as the conservative ‘pick-up’ method of lymphadenectomy have been trialled in gastric cancer [ 4 ], given the complexity of lymphatic drainage in this region, improved prognostic outcomes are correlated with an increased number of removed LNs [ 4 , 7 , 8 ]. Here, a greater number of removed LNs increases the chance of capturing the high-risk SLNs likely to contain metastases.…”
mentioning
confidence: 99%
“…Several meta-analyses have reviewed the safety of ICG and all determined there to be no significant risk to the injection of the compound [14,15]. One study even found that the use of ICG was associated with decreased intraoperative blood loss [16].…”
Section: Properties Of Icg and Description Of Intraoperative Usementioning
confidence: 99%